Association between Social Demographic Factors and Health Literacy in Jordan - Mohammad, Anber Abraheem Shlash; Alolayyan, Main Naser; Al- Daoud, Khaleel Ibrahim; Nammas, Yara Mahmoud Al; Vasudevan, Asokan; Mohammad , Suleiman Ibrahim (Journal of Ecohumanism, 2024)
The study highlights that low health literacy is a serious global health threat, causing health problem denial, poor communication with healthcare providers, and widening disparities. It aims to investigate how income, education, and socio-economic status affect health literacy levels. The study conducted an occasional design using quantitative data. This study was conducted using a structured questionnaire to obtain information from 413 randomly selected Ammani residents The questions were designed to assess the impact of health literacy level. The study's quantitative results show that socio-economic factors are the reasons for the health literacy among Amman residents, based on the 413 sample. Although gender only shows little differences, age, income, and education greatly affect health literacy, with those aged 30-60, higher income earners, and people with higher education levels having better understanding. It is necessary to design health literacy interventions for different demographic groups so as to eliminate the disparities and to get the so desired health outcomes. This study assesses the association between social demographic factors and health literacy in Jordan and found the level of literacy affected by social and economic factors, but in varying proportions for each topic with some recommendations.